PENGEMBANGAN BLOG SEBAGAI MEDIA PEMBELAJARAN ONLINE - Ardian Arief (AS-SALAM, 2013)
The development of the techology of information and communication hasin luenced the aspect of human living. That development can be seen from the kind of education which is based on technology. Applying technology of information and communication (TIK) is inally shown to the learning method in the schools and universities. One of the applications of the role of technology of information and communication in supporting to the learning process is by using blog.Blog is the application which is free of charge that can be used as one online-learning media. There are steps that need to be run in its developing: 1) making email; 2)making blog account; 3) making project menu, pro ile, download and information or according to necessary; 4) adapting with the level of learning.Developing blog as a media of Islamic learning in university is hoped to increase the understanding of Islamic learning in the level of university, also able to increase the knowledge of internet technology in this context of developing blog.